Pengenalan Jiwa Entrepreneur Pada Remaja Desa dengan Memanfaatkan Media Sosial dan E-Commerce - Mesran, Mesran; Imam Saputra; Guidio Leonarde Ginting; Suginam, Suginam; Dito Putro Utomo (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to examine and encourage the introduction of the entrepreneurial spirit in village teenagers by utilizing social media and e-commerce. In the current digital era, social media and e-commerce have become very effective tools to support business activities, including for teenagers living in rural areas. Through the use of social media, village teenagers can promote their local products to a wider market without being limited by geography. Meanwhile, e-commerce platforms provide easy access to sell and distribute their products efficiently. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews, participant observation, and document analysis. The research subjects were village teenagers who had utilized social media and e-commerce in their entrepreneurial activities. The research results show that the use of social media and e-commerce can increase the knowledge and business skills of village teenagers. In addition, they become more motivated to become entrepreneurs because they see larger market opportunities and the financial benefits that can be obtained. Apart from that, this research also found several challenges faced by village teenagers in utilizing social media and e-commerce, such as limited internet access and lack of technical knowledge. However, with the right training and guidance, these challenges can be overcome. Overall, this research concludes that introducing an entrepreneurial spirit through social media and e-commerce is an effective strategy for empowering village youth. This not only improves the local economy but also opens up new opportunities for the young generation in rural areas to develop and compete in the global market.